Pengaruh Metode Pembelajaran, Gaya Belajar dan Motivasi Belajar terhadap Hasil Belajar Siswa MI Roudlotul Mustashlihin Masangankulon Sukodono Sidoarjo - Fendi Pratama Putra; Eli Masnawati; Didit Darmawan (Journal on Education, 2024)
The learning method at MI. Roudlotul Mustashlihin Masangankulon has been using more expository models or approaches", or traditional such as lectures without a touch of creation and motivation, so that it cannot make students become active and rise to jump to find the potential that is within them and then develop it and this monotonous learning method certainly makes students passive, depressed, and as if he wanted to run away from his class. This study aims to explore the influence of learning methods, learning styles, and student motivation on student learning outcomes in MI. Roudlotul Mustashlihin Masangankulon. This study uses a quantitative research approach. According to Sugiyono (2016), the quantitative research approach is a research based on the philosophy of positivism, which is used to research certain populations and samples. while according to Arikunto (2013). The results showed that learning methods have a significant influence on student learning outcomes, showing that the application of innovative and interactive learning methods can increase student academic achievement. Second, students' learning styles also have a strong impact on learning outcomes, emphasizing the importance of understanding students' learning preferences and adapting learning strategies to suit their learning styles. Finally, learning motivation has a significant influence on student learning outcomes, suggesting that high levels of motivation can be a key factor in achieving academic success.